2017
DOI: 10.1002/cncr.31066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hospital safety net designation on treatment use and survival in hepatocellular carcinoma

Abstract: Patients at SNHs are less likely to undergo HCC treatment, even when diagnosed at an early stage, which likely contributes to worse survival. System-level differences in care delivery may partly explain racial/ethnic and socioeconomic disparities in HCC prognosis. Cancer 2018;124:743-51. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 31 publications
3
38
1
Order By: Relevance
“…High heterogeneity of intra-individual FC measurement has already been described. [4][5][6][7] We would like to alert clinicians to the measurement uncertainty of the FC assay within the same laboratory ( Figure 1A) and mostly among laboratories. Indeed, an external quality assessment by EQUALIS of 69 laboratories showed an inter-laboratory coefficient of variation about 42.6% for a target concentration of 174 mg/ g. Minimum was 49.5 mg/g, ie, at the limit of the pathologic threshold, and maximum was 287 mg/g, which is above the threshold used by Colombel et al This large variation is due, among others, to a high degree of stool heterogeneity, which was well-observed when we performed FC assays after extraction from a single location in the stool (Figure 1B and C).…”
Section: Preanalytical Heterogeneity In Fecal Calprotectin Measuremenmentioning
confidence: 99%
“…High heterogeneity of intra-individual FC measurement has already been described. [4][5][6][7] We would like to alert clinicians to the measurement uncertainty of the FC assay within the same laboratory ( Figure 1A) and mostly among laboratories. Indeed, an external quality assessment by EQUALIS of 69 laboratories showed an inter-laboratory coefficient of variation about 42.6% for a target concentration of 174 mg/ g. Minimum was 49.5 mg/g, ie, at the limit of the pathologic threshold, and maximum was 287 mg/g, which is above the threshold used by Colombel et al This large variation is due, among others, to a high degree of stool heterogeneity, which was well-observed when we performed FC assays after extraction from a single location in the stool (Figure 1B and C).…”
Section: Preanalytical Heterogeneity In Fecal Calprotectin Measuremenmentioning
confidence: 99%
“…Most, but not all, common medical and surgical disorders have worse outcomes in patients from distressed communities ( Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21] DOES LIVING IN A DISTRESSED COMMUNITY CAUSE WORSE OUTCOMES FROM SURGICAL PROCEDURES? Table 1 suggests that living in a distressed community is associated with worse outcomes from many medical disorders and from surgical interventions.…”
Section: How Do You Know If You Live In a Distressed Community?mentioning
confidence: 99%
“…Hepatocellular cancer 21 TAVR, Transcatheter aortic valve replacement; CABG, coronary artery bypass grafting.…”
Section: Urolithiasis 14mentioning
confidence: 99%
“…Management of HCC at a safety‐net hospital, where most patients are underinsured, uninsured, or utilize government insurance presents an additional challenge. Mokdad et al found that patients with HCC at a safety‐net hospital were less likely to undergo HCC directed treatment despite similar tumor stage at presentation. Additionally, of patients with localized disease, fewer received curative treatment at a safety‐net hospital than those at non–safety‐net hospitals …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, of patients with localized disease, fewer received curative treatment at a safety-net hospital than those at non-safety-net hospitals. 10 It is believed that screening patients who have HBV and HCV for hepatocellular carcinoma can improve survival. In a study by Zhang et al, 11 in patients with known HBV or chronic hepatitis, screening with AFP testing and ultrasound every 6 months led to a 37% reduction in HCC-associated mortality.…”
Section: Introductionmentioning
confidence: 99%